Bioresponsive Nanomedicine: The Next Step of Deadliest Cancers' Theranostics - Mao, Yuqiang; Liu, Xiaoying (Frontiers in Chemistry, 2020)
Among all cancers, lung, breast and prostate carcinoma are the three most fatal cancers. Although general therapeutic strategies and existent nanomedicine have been applied in relating cancer treatment, the side effects and potential damage induced by the off-target effect greatly lower the therapeutic efficiency. Recently, an increasing number of bioresponsive nanomaterials are recruited in fighting these deadliest cancers. Therefore, these latest bioresponsive nanomedicine are summarized in the current review. More specifically, the various novel nano-agents that could selectively respond to specific bio-conditions in malignant areas (e.g. pH, temperature, enzyme, Redox, elevated copper ion, etc.) are discussed in detail for their applications in cancer imaging (e.g. fluorescence, NIR, and MRI, etc.) and therapy (e.g. antiangiogenesis, chemotherapy, photothermal and chemodynamic therapy, etc.). The development of next-generation of bioresponsive nanomedicine and challenges involved are further discussed for future design.